Characterisation of Agr quorum sensing in Clostridium autoethanogenum - Piatek, Pawel (2018)
The Gram-positive, anaerobic, acetogenic bacterium Clostridium autoethanogenum is regarded as an important biocatalyst in the current advancement of industrial gas fermentation. The ever-widening diversity of industrially-relevant acetogenic bacteria has inspired a rational approach into utilising industrial waste gases as a viable feedstock, with goals of mitigating greenhouse gas emissions, and supporting an alternative means of fuel and high-value chemical production. Combined with this effort, is the expanding repertoire of gene editing tools that have allowed for the improvement of gas fermentation processes and increased spectrum of fermentative products. Despite these advances, there remain many pertinent questions, which addressed, can further the understanding of metabolism and physiology in acetogenic bacteria. This includes cell-to-cell communication and signalling, Quorum Sensing.